Marijuana use among adolescent Asian Americans and Pacific islanders: Analysis of ethnic subgroup and gender differences - Ting Luo; Christopher M. Anderson; Jijiang Wang; Yue-Lin Zhuang; Shu-Hong Zhu (Preventive Medicine Reports)
Objective: To assess heterogeneity in marijuana use among adolescent Asian American and Pacific Islander (AAPI) subgroups. Methods: AAPI high school students (n = 31,071) participating in the 2019–2020 California Student Tobacco Survey were categorized by race/ethnicity and examined for ever and current (past-30-day) marijuana use. Descriptive statistics were used to describe marijuana use and harm perceptions by subgroups. Multiple logistic regression was used to compare subgroups on marijuana use with other demographics as covariates. Results: Current marijuana use rates by ethnic subgroups were: Chinese 4.2 %, Koreans 4.9 %, Indians 5.2 %, Vietnamese 6.0 %, Hmong 6.4 %, Pakistanis 6.6 %, Japanese 9.4 %, Filipinos 9.6 %, Cambodians 17.9 %, other monoethnic Asians 10.5 %, and Pacific Islanders 22.3 %. Current use rates for monoethnic, multiethnic, and multiracial AAPIs were 7.3 %, 9.1 %, and 18.5 %, respectively, with multiracial AAPIs using at a higher rate than monoethnic and multiethnic AAPIs (both p's < 0.001). Among AAPIs overall, 11.3 % currently used marijuana. Females currently used at a higher rate than males, 10.8 % vs. 9.6 % (p = .011). Ever and current marijuana use were negatively correlated with perceptions that everyday and occasional use is harmful (all p's < 0.001). Compared to Chinese students, all subgroups except Koreans and Pakistanis were more likely to use marijuana (all p's < 0.05), with Filipinos, Japanese, Cambodians, and Pacific Islanders more than twice as likely (all p's < 0.001). Conclusions: There was substantial heterogeneity in marijuana use rates among ethnic subgroups of AAPI adolescents. Several AAPI subgroups used marijuana at elevated rates. Gender-based trendlines among AAPI adolescents have crossed.